USING A SONG AS A WAY TO DEVELOP LANGUAGE COMPETENCE IN TEACHING RFL (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-4-147-156Abstract. The study reports on the importance of working with song material in Russian as a foreign language classes. The article presents a methodological development that includes examples of tasks that can be used in the classroom. The tasks are aimed at developing lexical, grammatical, phonetic, sociolinguistic and cultural competencies. In addition, the tasks involve all types of speech activity, develop listening skills (students need to understand the general meaning of the text, hear the missing word), reading (read the text and understand its meaning), speaking and writing (answer questions in writing or orally), and also, the exercises are aimed at updating and consolidating lexical and grammatical skills and familiarization with facts about the culture and characteristics of the country of the language being studied. The presented materials can be used for training teachers of humanities and for conducting classes in the classroom of foreign students. The model described can be successfully applied in practice, and can also be used when developing lessons on other topics and songs.Key words: song, Russian as a foreign language, authentic material, interactive material, language competence